Microplastic exposure in anchovies: baseline evidence from small-island waters of Indonesia - Veronika Amelia Simbolon; Erpina Santi Meliana Nadeak; Demsa Simbolon; Ristina Rosauli Harianja (International Journal of Public Health Science (IJPHS), 2026)
Microplastics are emerging contaminants in aquatic environments and may enter human exposure pathways through seafood consumption. However, baseline exposure data for small pelagic fish in small-island settings remain limited, particularly in Indonesia. Anchovy (Stolephorus spp.), which is commonly consumed whole, may represent a direct dietary exposure pathway. This study aimed to quantify and characterize microplastic contamination in anchovy collected from Dendun Island waters. A descriptive cross-sectional study was conducted in 2025 using 100 anchovy samples obtained from local catches. Microplastics were extracted using oxidative digestion followed by density separation, filtration, and stereomicroscopic observation. Data were analyzed descriptively. A total of 109 microplastic particles were identified, with a mean abundance of 1.09 particles per individual. Fibres dominated (67.0%), followed by films (20.2%) and fragments (12.8%). Various colours were observed, indicating heterogeneous particle characteristics. This study provides baseline evidence of microplastic contamination in anchovy from a small-island coastal setting, highlighting its potential as a dietary exposure pathway. These findings support the need for routine monitoring and strengthened plastic pollution control strategies to protect seafood safety and public health.